The house of the seven gables - Hawthorne, Nathaniel, 1804-1864 ([Boston, Mass] : Thomson Heinle, 2007)
The gloomy old mansion has stood for hundreds of years in its small New England town, sheltering generations of the same unhappy family. Then Phoebe, the youngest member, comes to stay. Her winning ways and love help lift the mysteries and bring happiness to the family at last
Title from container
Keywords: Haunted houses -- Fiction; Families -- Massachusetts -- Salem -- Fiction; Salem (Mass.) -- Fiction